2020
DOI: 10.1038/s41467-020-14946-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in global groundwater organic carbon driven by climate change and urbanization

Abstract: Climate change and urbanization can increase pressures on groundwater resources, but little is known about how groundwater quality will change. Here, we use a global synthesis (n = 9,404) to reveal the drivers of dissolved organic carbon (DOC), which is an important component of water chemistry and substrate for microorganisms that control biogeochemical reactions. Dissolved inorganic chemistry, local climate and land use explained~31% of observed variability in groundwater DOC, whilst aquifer age explained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 56 publications
2
79
1
Order By: Relevance
“…Groundwater replenishment can occur either as diffuse recharge through the OM-rich soil zone or as indirect recharge originating from streams and wetlands that have the potential to contain high concentrations of OM. Despite the many sources of OM, groundwater dissolved organic carbon (DOC) concentrations are typically low (∼ 1 mg L −1 for the global median DOC concentration; McDonough et al, 2020a), suggesting significant processing in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater replenishment can occur either as diffuse recharge through the OM-rich soil zone or as indirect recharge originating from streams and wetlands that have the potential to contain high concentrations of OM. Despite the many sources of OM, groundwater dissolved organic carbon (DOC) concentrations are typically low (∼ 1 mg L −1 for the global median DOC concentration; McDonough et al, 2020a), suggesting significant processing in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…The source of such high concentration is assumed to be from surface vegetation, mobilized particulate organic matter and in-situ peat in that sandy environment (Meredith et al). This concentration is about 5 times higher than median global groundwater DOC concentration (McDonough et al, 2020a). X-ray Fluorescence spectrometry (XRF) analysis show that the major chemical composition of the soil is SiO2 (94%) while only 0.20% Fe2O3 is present.…”
Section: Factors Controlling Natural Hs Sorptionmentioning
confidence: 74%
“…Despite their interaction, natural organic matter (NOM) concentration in groundwater is much lower compared to rivers. The global median groundwater dissolved organic carbon (DOC) is only 1.0 mg C L -1 (McDonough et al, 2020a). This leads to questions such as where does the missing fraction go?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long residence times of DOC derived from surface environments in groundwater is unlikely because biodegradation, oxidation, and adsorption to mineral surfaces in the aquifer will decrease groundwater DOC concentrations over time. A recent study has demonstrated that there is a global negative correlation between groundwater residence times and groundwater DOC concentrations (McDonough et al, ). It is therefore more likely that old DOC in groundwater with high residence times is derived from the uptake of geological organic carbon (e.g., hydrocarbons, kerogen, or ancient DOC adsorbed to mineral surfaces in the sedimentary aquifer matrix), or the incorporation of inorganic carbon from carbonate weathering into microbial biomass (Fellman et al, ).…”
Section: Further Questions: Where Does Old Groundwater Carbon Come From?mentioning
confidence: 99%